That's me : Photographic Self-Images. - Kröger, Michael; Nachtigäller, Roland; Niemeyer, Thomas; Marta Herford, Herford (Herford : Marta Herford gGmbH, 2011)
Sherman, Cindy ; Schwarzkogler, Rudolf ; Klauke, Jürgen ; Export, Valie ; Makos, Christophe ; Krystufek, Elke ; Liebscher, Martin ; Kannisto, Aino
That's me Photographic Self-Images, MARTa Herford, Herford, 8 March - 8 May 2011
kunstcatalogus
Keywords: Sherman, Cindy; Schwarzkogler, rudolf; Klauke, Jürgen; Export, Valie; Krystufek, Elke; Liebscher, Martin; Kannisto, Aino